Використання напівпровідникових наноматеріалів як детекторних елементів хімічних органічних канцерогенів - Сушко, О. А. (ХНУРЕ, 2014)
This work describes the advantages of semiconductor QDs use as detector elements for organic substances with fused benzene rings in the sensors development. The use of QDs as detector elements of sensor device gives it advantages such as high selectivity, low detection limit (0.1 nM). Electrochemical and electrochemiluminescence studies of QDs on model systems have shown the possibility of such materials use as detectors in analytics for different physical nature objects control.
Keywords: напівпровідникові наноматеріали; детекторні елементи; хімічні органічні канцерогени